Improved reference genome for the domestic horse increases assembly contiguity and composition. (December 2018) - Kalbfleisch, Theodore; Rice, Edward; DePriest, Michael; Walenz, Brian; Hestand, Matthew; Vermeesch, Joris; O′Connell, Brendan; Fiddes, Ian; Vershinina, Alisa; Saremi, Nedda; Petersen, Jessica; Finno, Carrie; et al.
Abstract Recent advances in genomic sequencing technology and computational assembly methods have allowed scientists to improve reference genome assemblies in terms of contiguity and composition. EquCab2, a reference genome for the domestic horse, was released in 2007. Although of equal or better quality compared to other first-generation Sanger assemblies, it had many of the shortcomings common to them. In 2014, the equine genomics research community began a project to improve the reference sequence for the horse, building upon the solid foundation of EquCab2 and incorporating new short-read data, long-read data, and proximity ligation data. Here, we present EquCab3. The count of non-N bases in the incorporated chromosomes is improved from 2.33 Gb in EquCab2 to 2.41 Gb in EquCab3. Contiguity has also been improved nearly 40-fold with a contig N50 of 4.5 Mb and scaffold contiguity enhanced to where all but one of the 32 chromosomes is comprised of a single scaffold. Theodore Kalbfleisch et al. present an improved genome assembly for the domestic horse by combining short- and long-read data, as well as proximity ligation data. They improve contiguity of the assembly by 40-fold, with a 10-fold reduction in gaps.